879 Risks and management of airborne mercury levels at artisanal gold processing shops in the peruvian amazon. (24th April 2018) - Caravanos, Jack
Abstract : Gold mining using the mercury amalgamation process continues to present serious community and occupational exposure problems throughout the world. It is now estimated that 30% of all processed gold is produced using mercury amalgamation with over 10 million people involved in artisanal and small scale gold mining. In Peru there has been a 400% increase in the ASGM activities and is ranked 5th in worldwide gold production. It is estimated that one out of 28 people in Peru are associated with artisanal gold mining with Madre de Dios, an Amazonian State in Peru, accounting for 70% of mined gold. worker paper presents the results of mercury vapour area air sampling during the amalgam burning processing step where Hg/Au amalgam is heated and the mercury driven off as a vapour phase. Small-scale artisanal gold miners often do not have the equipment to burn off the mercury from the amalgam and resort to local shops for this service. These Compra de Oro shops can be found in villages along the Interoceanic Highway traversing Madre de Dios. A total of 16 Gold Shops were sampled in 5 villages along the Interoceanic Highway in Madre de Dios. In almost all cases, the worker exposure levels exceeded internationally accepted health standards. Results of workplace sampling will be presented as well as a discussion of efforts and challenges in managing occupational health risks in small-scale artisanal enterprises in low and middle-income countries.